(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Spinal tumor can occur in different anatomical location. Objective: The purpose of the present study was to see the demographic characteristics and anatomical location of spinal tumour. Methodology: This descriptive cross sectional study was conducted in the Department of Neurosurgery at National Institute of Neurosciences & Hospital, Dhaka, Bangladesh from January 2016 to December 2019 for a period of around 04 (four) years. Patients presented with spinal tumor were selected as study population. The demographics characteristics were evaluated among all the patients. Patients were examined by MRI for the detection of anatomical location of the tumor. Result: A total number of 57 spinal tumor cases were recruited for this study. The mean age with SD of the study population was 38.7±13.24 years. The male and female ratio was 1.34:1 Most of the spinal tumor were found in the thoracic region which was 29(50.9%) cases followed by lumbar region which was 20(35.1%) cases. Spinal tumor in cervical region was found in only 5(8.8%) cases. Conclusion: In conclusion adult middle age male patients are the most commonly suffering from spinal tumor which are mostly located in the thoracic region. Journal of National Institute of Neurosciences Bangladesh, 2020;6(1): 15-18